Lincoln at Gettysburg : the words that remade America - Wills, Garry, 1934- (New York : Simon & Schuster, 1992)
Examination of the Gettysburg Address and Lincoln in their historical moment and cultural frame breathing new life into the words and revealing much about the President.
"A Touchstone book."
Includes bibliographical references (p. 267-304) and indexes.
Young Adult.
Young Adult
Keywords: Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Oratory; Lincoln, Abraham, -- 1809-1865.